A simple and easy-to-prepare imidazole-based probe for the selective chromo-fluorogenic Cu(II) detection in aqueous environments - Okda, H. E. (2017)
Synthesis and evaluation of the chromo-fluorogenic chemosensor ability of imidazole derivatives in organic solventes and in aqueous media.